1979
DOI: 10.1007/bf01541215
|View full text |Cite
|
Sign up to set email alerts
|

Treatments of premature ejaculation and psychogenic impotence: A critical review of the literature

Abstract: Research on the treatments of premature ejaculation and psychogenic impotence is reviewed. Problems with the existing definitions of these disorders are discussed. The studies are reviewed under seven major headings: depth therapies, behavior therapies, hypnosis, drug therapy, mechanotherapy, reeducative and supportive therapies, and extensive retraining programs. Most of the studies were case reports. Considerable methodological weaknesses were found, most notably the failure to specify subject and treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

1980
1980
2013
2013

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(15 citation statements)
references
References 51 publications
0
13
0
2
Order By: Relevance
“…Nomination of an exact threshold stopwatch IELT cutoff point for diagnosis of PE is an integral part of the inclusion criteria for a clinical trial. There is considerable variance of the latencies used to identify subjects with PE with IELTs that range from 1 to 7 minutes [35][36][37][38][39][40][41][42][43][44][45][46]. These IELT cutoff points include ejaculation 1 minute after vaginal intromission [40], 2 [41,44], 3 [43], 4 [37], 5 [36,38,42], and 7 minutes [39].…”
Section: Baseline Ejaculatory Latency Time (Elt)mentioning
confidence: 99%
“…Nomination of an exact threshold stopwatch IELT cutoff point for diagnosis of PE is an integral part of the inclusion criteria for a clinical trial. There is considerable variance of the latencies used to identify subjects with PE with IELTs that range from 1 to 7 minutes [35][36][37][38][39][40][41][42][43][44][45][46]. These IELT cutoff points include ejaculation 1 minute after vaginal intromission [40], 2 [41,44], 3 [43], 4 [37], 5 [36,38,42], and 7 minutes [39].…”
Section: Baseline Ejaculatory Latency Time (Elt)mentioning
confidence: 99%
“…IELT is defined as the time between vaginal intromission and intravaginal ejaculation [11]. Although it has been suggested that an IELT of 2 minutes or less may serve as an adequately sensitive criterion for defining PE [7], a standard cut‐off for ejaculatory latency does not exist, and studies have used latency values ranging from 1 to 7 minutes for defining PE [2,7,9,12–18].…”
Section: Introductionmentioning
confidence: 99%
“…The therapist carefully chooses the environment and atmosphere, with patients and therapists on large cushions, using a friendly relationship on first-name terms, and involving non-erotic massages and role-playing. Hypnosis [32] , mechanotherapy [33] , re-educative and supportive therapies, and the extensive training programmes described elsewhere as alternatives to behavioural therapies, all suffer from considerable methodological weaknesses, a failure to specify subject and treatment variables, inadequate or non-existent control groups, a limited follow-up, and failure to obtain the partner’s validation of the patient’s progress [34] .…”
Section: Psychological Therapies For Pementioning
confidence: 99%